Recycled Concrete Used in Subbase in Potential Use for Road Base and Cement Bounded Material (CBM) - Ahmad, Hassan Haidar (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Structure life cycle and economic developments in Qatar can lead to reconstruction as well as demolition of structures such as buildings and roads. One of the main wastes from demolition work is concrete and reinforced concrete. Concrete dumped as waste in landfills in Qatar, so this paper will emphasis utilizing the concrete waste through means of recycling and reusing in the road construction market. Qatar’s benefit is to decrease pollution, generating economic benefits and become more self-sustainable and save its existing resources. This paper will focus on the fine recycled concrete (FRC) 0-5 mm as a fine aggregate material in the mix design for constructing the base road layers under the Asphalt layers and how using crushed concrete can increase the quality and change the classification of the base aggregate mixes. After the process of concrete crushing, the crushed material will be produced and used as fine aggregate in a fixed amount of fine crushed concrete which can improve the properties of the mix design for base road construction (aggregate base) produced in different production dates. This can decrease the use and import of sand (dune sand and washed sand) from overseas, in the mix designs for Subbase, Road Base and Cement bounded material (CBM) and increase the quality in Qatar. The paper will verify the use of fine crushed concrete (FRC) in the aggregate mixes to upgrade the quality of the fine aggregate material used in the road construction (Goonan, 1998).